Effects of a nonlinear pedagogy intervention programme on the emergent tactical behaviours of youth footballers. (4th July 2019) - Práxedes, Alba; Del Villar Álvarez, Fernando; Moreno, Alberto; Gil-Arias, Alexander; Davids, Keith
ABSTRACT: Purpose: This study analysed the effects of a training intervention programme using principles of Non-Linear Pedagogy (NLP) on the decision making (DM) and performance behaviours (P) of youth footballers. Method: 19 footballers (U12 yrs) participated in 14 training sessions, spread over three phases: Pre-intervention, Intervention, Retention. The intervention was based on Small-Sided and Conditioned Games. We assessed progress during the intervention phase at two different points: intermediate and final. The GPET instrument was used to analyse the DM and P during the completion of 3208 passes in the intervention. Results: Results shown significant improvements in the DM and P after the intermediate and final points of the acquisition phase. Moreover, significantly higher values were also obtained in both variables in the retention, compared to the pre-intervention phase. Conclusion : Results indicated that the NLP intervention programme was effective in improving both aspects of team games performance in youth players, with effects consolidated over time.